Biodiversity, natural products and cancer treatment - Kuete, Victor; Efferth, Thomas (Singapore : World Scientific, 2014)
This book is the first of its kind in bringing together biodiversity, chemical ecology, phytochemistry and cancer therapy. The highlight of the book is an exhaustive compilation of scientific data on biodiversity of medicinal plants, biodiversity and metagenomics, chemical ecology of medicinal plants, chemical ecology of marine organisms, natural products from terrestrial microbial organisms with activity towards cancer cells, marine organisms, ethnopharmacology and phytotherapy, contribution of African flora in world fight against cancer, natural products derived from terrestrial plants with.
Includes bibliographical references and index.
Keywords: Biodiversity; Biological Products -- therapeutic use